The Psychological Impact of the Coronavirus Disease 2019 Pandemic on Pregnant Women in China - Zheng, Zheng; Zhang, Ruoxi; Liu, Tao; Cheng, Pei; Zhou, Yanhong; Lu, Weicong; Xu, Guiyun; So, Kwok-Fai; Lin, Kangguang (Frontiers in Psychiatry, 2021)
Background: The coronavirus disease 2019 (COVID-19) pandemic has been reported to have negative psychological impact on mental health. Nonetheless, there are few studies investigating the impacts on pregnant women. This study investigated the psychological impact of COVID-19 pandemic on pregnant women, and the associated risk factors that moderated this impact. Methods and Materials: A total of 2798 pregnant participants were recruited from the Guangzhou Women and Children’s Medical Center. The Patient Health Questionnaire-9 (PHQ-9), Generalized Anxiety Disorder-7 (GAD-7) and Insomnia Severity Index (ISI) were used to assess depression, generalized anxiety disorder and insomnia, respectively, during and before the COVID-19 pandemic. The Impact of Event Scale-Revised (IES-R) was used to assess psychological stress during theCOVID-19 pandemic. Results: During the COVID-19 pandemic, over one third of pregnant participants reported mild depression, around 20% experienced mild generalized anxiety, about one third reported problems with sleeping, and more than 15% felt mild psychological stress. The occurrence of psychological problems was significantly higher during the COVID-19 pandemic when compared to before the outbreak. The previously described pattern that pregnant women in the first trimester are more likely to report depression, and those in the third trimester are more likely to report insomnia and psychological stress, was also recognized in our study population. Mental health issues existing before the outbreak were risk factors, while family support was a protective factor in the occurrence of the measured mental health problems during the COVID-19 pandemic. Conclusion: Our data suggest pregnant women’s mental health is inevitably affected during the COVID-19 pandemic. Pregnant women in the first and third trimester and those who experienced mental issues before the outbreak may be particularly affected. Keywords: anxiety, COVID-19, depression, pregnant women, stress